STRENGTHENING STUDENT CAPACITY IN THE PUBLICATION OF SCIENTIFIC PAPERS - Siti Rahayu Nasichatu Muslimatin; Muchamad Suradji (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2023)
The purpose of this study is to determine the strengthening of student capacity in writing scientific papers. The research method used is qualitative descriptive research, as for the power collection techniques used include; observation, interviews and documentation. Data analysis using qualitative analysis with steps in data analysis techniques include: data reduction, data display and verification. The results of the study can be explained that this study tries to direct the writing of scientific papers to publication. Publications can be in the form of articles, learning modules or book chapters. This is an obligation for lecturers and students in order to improve the quality and quantity of publications on campus. Thus, the implementation process of the tri dharma of higher education must be directed to outputs that can be published. Although it is considered less than optimal, the improvement process continues to be carried out by the campus to meet the publication rules. This improvement is carried out by providing training in writing scientific papers and publications as a form of campus efforts in terms of publication. Strengthening student capacity is also the main task target because it needs more training in terms of writing and publication